The educational roots of trust - Borgonovi, Francesca (OECD Publishing, 2015)
Trust is important for social and economic well-being, for enhancing social cohesion and strengthening resilience, and for maintaining security and order in our societies. Trust is the foundation upon which social capital is built and it also is intimately related to human capital. This work examines the association between education and levels of interpersonal trust, using data from the OECD's Survey of Adult Skills (PIAAC). Our analysis demonstrated that education strengthens the cognitive and analytical capacities needed to develop, maintain, and (perhaps) restore trust in both close relationships as well as in anonymous others. It does so both directly, through building and reinforcing literacy and numeracy in individuals, and indirectly, through facilitating habits and reinforcing behaviours such as reading and writing at home and at work. Education and trust are thus fundamentally intertwined and dependent on each other. While all countries across the OECD have been striving to improve their education systems in terms of student achievement levels, this analysis suggests that there are also concrete elements that could be usefully addressed in order to reinforce and strengthen trust
Keywords: Education